Deconstructing Prinz’s moral theory - de Mesquita Silveira (UCS), Matheus (Controvérsia (UNISINOS) - ISSN 1808-5253, 2016)
This paper focuses in an explanation of Prinz’s moral proposal in the book The Emotional Construction of Morals, specific in the role that emotions and sentiments play in his system. The first part relates to the presentation and explanation of his two main theses, namely, a metaphysical and an epistemic approach of morality. A good understanding of the main concepts worked by the author may shine a light in what he understands as morality, providing a better view of how and when he turns away from naturalism, despite of the large number of empirical studies that he presents in his book. The result of this paper will be a better understanding of the position he defends and how his approach is a deception in terms of a naturalistic view of morality, arguing that his theses are, at the end, an empirically disguised culturalism.